Bioenergie im Spannungsfeld Wege zu einer nachhaltigen Bioenergieversorgung - Ruppert, Hans; Ibendorf, Jens (Universitätsverlag Göttingen, 2017)
The challenge of this interdisciplinary research on sustainable bioenergy production in rural areas is how to reconcile the chances and risks of bioenergy production within the context of climate stabilization, resource conservation, biodiversity, water, air, and soil preservation, the interests of society and of farmers. To answer this we developed and improved evaluation criteria and methods for a bioenergy implementation in rural areas. We show that the problems arising from energy plant production such as monoculture, changes of landscape and land use competition, loss of biodiversity, costs, social denial etc. may be eliminated during workshops with the main stakeholders (farmers, technicians, policymakers, administration, ecologists etc.) as well as with interested people. We created some tools to facilitate decision-making and consensus building. Especially the decision behaviour of farmers for or against bioenergy is investigated. Some results from our field research: Energy plants may increase the richness in species on farmland. Contaminated areas should be utilised to grow energy plants with low extraction efficiency for pollutants. Emissions from wood and straw burning can be strongly minimised.